Preventing Auschwitz: Teaching the Holocaust from a photografic exhibition - Corchado Guillén, David (Clio. History and History Teaching, 2022)
Teaching the Holocaust in Secondary Education is a non-renounceable and complex task, due to its condition of extreme and almost ineffable event. The treatment of History from the point of view of the defeated and of memory as a mobilizing tool offer very valuable educational possibilities for dealing with the teaching of the Holocaust. The same is true of education in democratic values, which is a necessary task in the current context of a renaissance of neo-fascist and extreme right-wing movements, and the trivialization and denial of the Jewish genocide. For this purpose, photography is presented as a useful primary source of information to bring the historical method to the classroom and as a motivating didactic resource in a society hyper-saturated with images.